2016
DOI: 10.4103/0971-9261.176941
|View full text |Cite
|
Sign up to set email alerts
|

The extended Kasai portoenterostomy for biliary atresia: A preliminary report

Abstract: Aims:In 1955, Professor Morio Kasai first performed a hepatic portoenterostomy. Since then, the procedure has changed the lives of children with biliary atresia (BA). We report our initial experience in performing “extended” Kasai portoenterostomy (KPE), a modification of the original procedure.Materials and Methods:Since 2013, we have used the technique of “extended KPE” and prospectively recorded data on all children undergoing this operation. Data on demographics, clinical features, liver function tests, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 18 publications
1
6
0
1
Order By: Relevance
“…In a Japanese study, the rate of early jaundice clearance was 57% and the 10-year survival rate with their native liver was 54% [8]. Various studies from India have reported 36.2-47.2% of early jaundice clearance [9][10][11]. Our group reported successful KPE in a 29.4% of children over 90 days of age and concluded that in the absence of synthetic liver failure, age should not be a disqualification for performing KPE [12].…”
mentioning
confidence: 61%
“…In a Japanese study, the rate of early jaundice clearance was 57% and the 10-year survival rate with their native liver was 54% [8]. Various studies from India have reported 36.2-47.2% of early jaundice clearance [9][10][11]. Our group reported successful KPE in a 29.4% of children over 90 days of age and concluded that in the absence of synthetic liver failure, age should not be a disqualification for performing KPE [12].…”
mentioning
confidence: 61%
“…Analysis of IOC services data in the context of cholecystectomy assumes IOC is only performed during cholecystectomy surgery. However, hepatoportoenterostomy in children would require an IOC but no cholecystectomy, 16 meaning that inclusion of services for children would artificially inflate IOC rates. Accordingly, service claim data for children aged 0–4 and 5–14 years were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…[ 6 7 ] Conversely, few infants presenting after 90 days of age can also benefit from KPE. [ 4 8 ] Hence, grade of “liver fibrosis” is the guiding principle for KPE rather than “age.”[ 4 ] Hence, its “age” versus “liver fibrosis” at presentation and the latter appears to be the critical prognostic indicator. However, in most centers across the world, majority of BA cases are subjected to KPE without the evaluation for grade of 'liver fibrosis'.…”
Section: T Iming and T Ype Of Smentioning
confidence: 99%
“…KPE is a palliative surgery; several modifications have improved “Jaundice Disappearance Rate” (JDR) and prolonged NLS;[ 8 ] however, both depend on the grade and “rate” of progressive liver fibrosis, pre- and post-KPE, respectively. The progressive liver damage can continue despite the “so-called” successful KPE, slowly in cases with adequate bile flow and rapidly in cases with no bile flow, leading to decompensated cirrhosis requiring early sequential LT.[ 1 ]…”
Section: F Ollow-up and I Ndications Of mentioning
confidence: 99%